Bahaya pada Masa Remaja - Cindy Azkhya; Raihanah Muttmainnah; Nabilla Zahara; Linda Yarni (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
This article discusses the dangers faced by teenagers, both physically and psychologically. Adolescence is an important transition period in an individual's life, where they experience various physical, emotional and social changes. This article outlines some of the physical dangers that teenagers face, such as the risk of death, suicide attempts, physical disabilities, and problems with awkwardness or stiffness. Additionally, psychological dangers are discussed, including immature social behavior, risky sexual behavior, and conflict in family relationships. It is important to understand that these dangers can have a significant impact on a teenager's development and well-being. Therefore, this article also explores the implications of adolescent development in the context of counseling services, including the importance of emotional development, moral education, religious awareness, creativity, and political awareness. In conclusion, this article highlights the complexity of adolescence and the importance of appropriate interventions in supporting positive adolescent development.